ROLE OF SERIN/ THREONINE KINASE INHIBITOR IN THERAPY NON-ALCOHOLIC STEATOHEPATITIS AND ALCOHOLIC HEPATITIS - Novriantika Lestari (Jurnal Kedokteran dan Kesehatan, 2019)
Liver fibrosis is a reversible response to a wound healing with marked accumulation of extracellular matrix which caused by injury to the liver. Liver fibrosis can be caused by various factors including alcohol and non-alcohol steatohepatitis. The process of fibrosis serves to localize the inflammation during chronic exposure. The hepatic stem cell (HSC) has a key role in the pathogenesis of liver fibrosis. The HSC activation is characterized by increased profibrogenic mediators including members of the TGF-? superfamily. In order to enable signal transduction, the mediator needs to bind to its receptors. The serine/ threonine kinase receptor is a receptor that binds to the TGF-? superfamily ligand, including TGF-?, BMP, activin and other mediators. The ligand receptor-binding activity will stimulate signal transduction that will translocate into the nucleus and phosphorylate various transcription factors that play a role in cell proliferation, differentiation, or apoptosis. There is currently no standard therapy for liver fibrosis. Based on the central role of the serine/ threonine kinase receptor in the pathogenesis of liver fibrosis, it is thought that the use of serine/ threonine kinase inhibitors is a promising therapy.